Pengaruh Fasilitas dan Layanan Komunikasi terhadap Kepuasan Mahasiswa di Universitas HKBP Nommensen Pematangsiantar - Hilma Harmen; Beresman Siburian; Dora Pitaloka; Diana Dongoran; Bella Amelia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to evaluate the influence of facilities and communication services on student satisfaction in educational institutions. Through quantitative analysis, this research highlights the importance of facilities and communication services in shaping a satisfying learning experience for students. The sample in this study consisted of 89 students from the 2023 cohort at Universitas HKBP Nommensen Pematangsiantar. This research employs a quantitative method by collecting data through observation and questionnaires distributed to willing participants. The data were analyzed using SPSS. The results of the study indicate that the facilities variable has a positive and significant influence on satisfaction, and the communication services variable also affects satisfaction.